A TESTING PRONUNCIATION AND ITS IMPORTANCE IN THE USE OF ENGLISH LANGUAGE TEACHING - Usein, Arafat (International Scientific Journal Vision, 2019)
The evaluation of students’ pronunciation is not given the place it deserves in many EFL and ESL classes. Yet, it’s known and generally accepted that the purpose of testing pronunciation is not only to evaluate knowledge and award grades, but also, and probably more importantly, to motivate students to be sensitive to this aspect of English. Given that the motivation of many students for learning English is instrumental rather than integrative, pronunciation tends to be neglected by many learners as long asthey know they will not be tested on it. English may be one of the most difficult languages in the world to pronounce. Therefore, teaching English Pronunciation from the beginning should be treated equally with Speaking, Listening, Reading and Writing.